Dnmt3a-mediated hypermethylation of FoxO3 promotes redox imbalance during osteoclastogenesis - Wei Zhang; Wenming Li; Jun Du; Chen Yang; Lei Yu; Peng Yang; Haifeng Zhang; Zebin Wu; Gaoran Ge; Huilin Yang; Dechun Geng (Proceedings of the National Academy of Sciences, 2025)
Redox imbalance contributes to aberrant osteoclastogenesis and osteoporotic bone loss. In this study, we observed lower Forkhead box protein O3 (FoxO3), a transcription factor associated with cellular oxidative stress, enhanced osteoclastogenesis in osteoporosis (OP). Single-cell RNA sequencing (scRNA-seq) analysis on the human femoral head indicated that FoxO3 is widely expressed in macrophages. Furthermore, Lysm-Cre;FoxO3 f/f OVX mice showed increased reactive oxygen species (ROS), enhanced osteoclastogenesis, and more bone loss than normal OVX mice. Mechanistically, we identified FoxO3 promoter methylation as a crucial factor contributing to decreased FoxO3, thereby influencing osteoclastogenesis and OC function. Intriguingly, we observed that Dnmt3a, highly expressed during osteoclastogenesis, played a pivotal role in regulating the methylation of the FoxO3 promoter. Knockdown of Dnmt3a promoted FoxO3 expression, inhibiting osteoclastogenesis and mitigating OP. Interestingly, we observed that Dnmt3a alleviated osteoclastogenesis by suppressing ROS via upregulating FoxO3 rather than inducing the dissociation of RANK and TRAF6. Collectively, this study elucidates the role and mechanism of FoxO3 in osteoclastogenesis and OP, providing a epigenetic target for the treatment of OP.